2007
DOI: 10.1016/j.bbrc.2007.06.148
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of MCP-1/CCR2 pathway ameliorates the development of diabetic nephropathy

Abstract: Monocyte chemoattractant protein (MCP-1) is an important mediator for macrophage recruitment in atherosclerosis and various glomerulonephritis. However, the role of MCP-1 and its receptor CCR2 in the progression of diabetic nephropathy remains unknown. Using a type 1 diabetic nephropathy model that shows noticeable glomerulosclerosis, we examined the role of MCP-1/CCR2 by propagermanium (Pro; CCR2 antagonist) treatment, and confirmed it by transfection of plasmids carrying the 7ND (a mutant of MCP-1) gene. We … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
107
0
3

Year Published

2009
2009
2020
2020

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 156 publications
(114 citation statements)
references
References 22 publications
4
107
0
3
Order By: Relevance
“…The macrophage has been presumed to be a critical mediator of diabetic nephropathy [36][37][38], and blockade of the MCP-1/CC chemokine receptor 2 system in diabetic mice leads to reduced albuminuria, mesangial expansion and macrophage infiltration [39][40][41][42]. Secretory factors from macrophages may cause histological and functional changes in glomeruli.…”
Section: Discussionmentioning
confidence: 99%
“…The macrophage has been presumed to be a critical mediator of diabetic nephropathy [36][37][38], and blockade of the MCP-1/CC chemokine receptor 2 system in diabetic mice leads to reduced albuminuria, mesangial expansion and macrophage infiltration [39][40][41][42]. Secretory factors from macrophages may cause histological and functional changes in glomeruli.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, disruption of the CCR2 pathway has already been considered for the treatment of atherosclerosis, inflammation, rheumatoid arthritis and multiple sclerosis [32]. In addition, several pre-clinical studies also have shown promise for CCR2 inhibition including protective effects on diabetic nephropathy [33], renal fibrosis [31], and high-fat diet-induced insulin resistance and glucose intolerance [17]. However, it is worth noting that the complete absence of CCR2 probably has detrimental effects.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, genetic deficiency of molecules facilitating leucocyte recruitment (e.g. Icam1, Ccl2) and pharmacological blockade of chemokine CC motif receptors (CCR) 1 and 2 can reduce macrophage accumulation and renal injury in mouse models of diabetic nephropathy [6,[9][10][11][12]. However, these approaches are limited in that they do not target macrophages selectively, restricting the interpretation of these findings.…”
Section: Introductionmentioning
confidence: 99%